Prehistoric land degradation in Hungary : who, how and why? - Willis, K. J.; Braun, M.; Sümegi, P.; Bennett, K. D.; Tóth, A.; Sümegi, P.; Tóth, A.
The recent study of Kis-Mohos Tó lake in Hungary reveals an important sequence of prehistoric landscape changes from the earliest land clearance to the early Middle Ages. The recognition of land degradation, through the application of new analytical methods, forms an important part of the discussion.